IN VITRO ANTIFUNGAL ACTIVITY OF POTASH ALUM AGAINST CANDIDA ALBICANS ON ACRYLIC RESIN - Irshad, Muhammad; Younas, Muhammad; Shabir, Hina; Alam, Muhammad Shiraz; Rehman, Zia Ur; Aleem, Saima (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the in vitro antifungal activity of Potash Alum (Phitkary) solution on Candida Albicans growth on heat cured acrylic resin.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Oral Pathology, Peshawar Dental College, Peshawar, from Nov 2019 to Jan 2020.Methodology: Acrylic resin discs (n=120) of standard size were prepared following the manufacturer’s instructions. The acrylic discs were contaminated with a suspension of 106cfus/ml of C. albicans in Sabouraud dextrose broth for 24 hours. After contamination, 30 acrylic discs were randomly selected, washed, sonicated, and plated for colony counts. The remaining 90 acrylic discs were randomly divided into 3 groups, 30 acrylic discs in each group. Group A discs were kept in 5.25% Sodium Hypochlrite solution, group B discs were kept in sterile Phosphate Buffered Saline and group C discs were kept in Potash-alum solution (10mg/ml). After 2 hours, all discs were washed, sonicated, and cultured on Sabouraud dextrose agar in serial dilutions for colony counts. Data was analysed using SPSS version-19.Results: Both Potash Alum (10 mg/ml) and Sodium Hypochlorite were effective in completely removing the attached Candida cells from the acrylic resin. In contrast, the negative control was only able to reduce viable counts by 23.6%. Sodium Hypochlorite and Potash Alum both showed statistically significant activity (p